(untitled) (Al-Aasar, 2025)
Education plays a crucial role in the upbringing of students, society, and the state. The contemporary era presents two forms of education that include: (i) Contemporary modern education and (ii) Religious education. It is pertinent to highlight that both of the education systems do not meet the requirements of present-day society, for precedent, the religious or Madrasa education that has been provided to students for ages failed to provide the current skills and knowledge. Contemporary modern education that has been provided in our school system lacks socialization, religious upbringing, and cultural and ethical values. “Education in Islam has twofold aims that include: (i) Acquiring intellectual knowledge (through the application of reason and logic), and (ii) Developing spiritual knowledge (derived from drive revelation and spiritual experience (. Islam provides equal opportunities for males and females to gain an education. Acquiring knowledge in Islam is not intended as an end but as a means to stimulate a more elevated moral and spiritual consciousness, leading to faith and righteous action.” [1] The article explores the education system of the state in the light of the Quran and Seerah, which includes (i) the Definition of education and state, (ii) the Concept of education in the light of the Quran, (iii) the Teaching methodology of the Holy Prophet (Peace Be Upon Him); (iv) Analytical view of modern education and Islamic teaching.